Attention without awareness in blindsight. - Kentridge, R; Heywood, C; Weiskrantz, L (1999)
The act of attending has frequently been equated with visual awareness. We examined this relationship in 'blindsight'--a condition in which the latter is absent or diminished as a result of damage to the primary visual cortex. Spatially selective visual attention is demonstrated when information that stimuli are likely to appear at a specific location enhances the speed or accuracy of detection of stimuli subsequently presented at that location. In a blindsight subject, we showed that attention can confer an advantage in processing stimuli presented at an attended location, without those stimuli entering consciousness. Attention could be directed both by symbolic cues in the subject's spared field of vision or cues presented in his blind field. Cues in his blind field were even effective in directing his attention to a second location remote from that at which the cue was presented. These indirect cues were effective whether or not they themselves elicited non-visual awareness. We concluded that the spatial selection of information by an attentional mechanism and its entry into conscious experience cannot be one and the same process.